2017
DOI: 10.1002/hed.24783
|View full text |Cite
|
Sign up to set email alerts
|

Local resectability assessment of head and neck cancer: Positron emission tomography/MRI versus positron emission tomography/CT

Abstract: Both contrast-enhanced PET/MRI and contrast-enhanced PET/CT can serve as reliable examinations for defining local resectability of head and neck cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 29 publications
1
26
0
1
Order By: Relevance
“…In addition, the following quantitative PET‐based parameters of the primary tumor were assessed: maximum standardized uptake value (SUV max ) and metabolic tumor volume (MTV). Our selection of parameters is based on previously published literature and several decades of experience in a tertiary‐care hospital serving as a national reference center for head and neck cancer …”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, the following quantitative PET‐based parameters of the primary tumor were assessed: maximum standardized uptake value (SUV max ) and metabolic tumor volume (MTV). Our selection of parameters is based on previously published literature and several decades of experience in a tertiary‐care hospital serving as a national reference center for head and neck cancer …”
Section: Methodsmentioning
confidence: 99%
“…With the recent introduction of FDG‐PET/MR, some CT‐related problems in the oropharynx that also exist in FDG‐PET/CT, for example, dental artifacts, could be improved. For assessing the resectability of the primary tumor, several studies showed that both hybrid imaging modalities—FDG‐PET/CT and FDG‐PET/MR—are reliable tools . The clinical assessment of HNSCC usually relies on triple endoscopy, which incorporates an examination of the upper aerodigestive tract with rigid or flexible instruments under general anesthesia and a systematic digital palpation of the pivotal subsites.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations